Gene-Environment Effects on Female Fertility - Nicola Barban; Elisabetta De Cao; Marco Francesconi (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2021)
Fertility has a strong biological component generally ignored by economists. Using the UK Biobank, we analyze the extent to which genes, proxied by polygenic scores, and the environment, proxied by early exposure to the contraceptive pill diffusion, affect age at first sexual intercourse, age at first birth, completed family size, and childlessness. Both genes and environment exert substantial influences on all outcomes. The anticipation of sexual debut and the postponement of motherhood led by the diffusion of the pill are magnified by gene-environment interactions, while the decline in family size and the rise in childlessness associated with female emancipation are attenuated by gene-environment effects. The nature-nurture interplay becomes stronger in more egalitarian environments that empower women, allowing genes to express themselves more fully. These conclusions are confirmed by heterogeneous effects across the distributions of genetic susceptibilities and exposure to environmental risks, sister fixed effects models, mother-daughter comparisons, and counterfactual simulations.
Keywords: D10; I14; I15; J01; J13; J16; 330; Fertility; Genetics; Polygenic Score; Contraceptive Pill; Nature versus Nurture; Social Norms